A complex twintron is excised as four individual introns. - Drager, R G (1993)
Twintrons are introns-within-introns excised by sequential splicing reactions. A new type of complex twintron comprised of four individual group III introns has been characterized. The external intron is interrupted by an internal intron containing two additional introns. This 434 nt complex twintron within a Euglena gracilis chloroplast ribosomal protein gene is excised by four sequential splicing reactions. Two of the splicing reactions utilize multiple 5'- and/or 3'-splice sites. These findings are evidence that introns with multiple active splice sites can be formed by the repeated insertion of introns into existing introns.